The Effective Regulation of Tobacco Use in Japan - Pitt, Hamish (2006)
Internationally, controls over the consumption of tobacco have reached unprecedented levels. The toughest controls have generally been implemented in those countries with the highest GDPÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂÃÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¬ÃÂÃÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂ¬ÃÂ¾ÃÂÃÂ¢s. Japan, however, is an exception: although the country is the worldÃÂÃÂÃÂÃ¢ÂÂÃÂÃ¢ÂÂ ÃÂ¢Ã¢ÂÂ¬Ã¢ÂÂ¢ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂÃÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¬ÃÂÃÂÃÂÃ¢ÂÂÃÂÃÂ¢ÃÂ¢Ã¢ÂÂÃÂ¬ÃÂÃÂ¡ÃÂÃÂÃÂ¢Ã¢ÂÂ¬ÃÂ¡ÃÂÃÂ¢ÃÂ¢Ã¢ÂÂ¬ÃÂ¾ÃÂÃÂ¢s second-largest in economic terms, it sustains one of the highest cigarette consumption rates in the world and has shown slow progress in enforcing controls over cigarette sale, ingredient disclosure and public smoking.